Investigation into the formation of PAHs in foods prepared in the home to determine the effects of frying, grilling, barbecuing, toasting and roasting. (April 2015) - Rose, Martin; Holland, Joe; Dowding, Alan; Petch, Steve (R.G.); White, Shaun; Fernandes, Alwyn; Mortimer, David
Highlights: The effects of cooking on the formation of 27 different PAHs in foods were investigated. Little evidence of PAH formation during the grilling, frying, roasting and toasting. Barbecuing with charcoal plus wood chips however resulted in the formation of PAH in most foods. Abstract: The effects of frying, grilling, barbecuing, toasting and roasting on the formation of 27 different PAHs in foods were investigated. A total of 256 samples from in-house cooking experiments were produced. There was little evidence of PAH formation during the grilling, frying, roasting and toasting experiments. Comparison with the raw materials used in the experiments showed little or no increase in PAH concentrations for all of the sample types, regardless of distances from the heat source, cooking mediums and intensity of cooking conditions. Barbecuing with charcoal plus wood chips however resulted in the formation of benzo[ a ]pyrene in most foods; for beef burgers only, barbecuing over charcoal (without the use of wood chips) gave the highest levels. In general PAH levels increased when the food was barbequed closer to the heat source. For sausages cooked over briquettes, and for beef burgers, beef and salmon cooked over charcoal, the concentration of PAHs was lower when the food was closer to the heat source. Cooking time may result in a moderate increase of PAHs in some foods, although concentrations in beef burgers appeared to fall when cooking time was extended by 50–100%.